KAJIAN HADIS PERSPEKTIF SUNI DAN SYIAH: Historisitas, Kehujahan Hadis, Parameter Kesahihan Hadis dan Keadilan - Rahmat Miskaya; Noor Said Ahmad; Umi Sumbulah; Moh. Toriquddin (IAIN Syekh Nurjati Cirebon, 2021)
This article discusses the discourse of hadith in the Sunni and Shi’ah traditions, covering aspects of historicity, classification, parameters, and hadiths among these two major schools of Islam. There are very striking differences regarding the position of the Prophet as the source of hadith, the distribution of hadiths, the justice and credibility of the companions, the criteria for the validity of hadith, and so on. In the Sunni view, one of the requirements of the sahih hadith is that the sanad is continuous from narrator to Rasul without being interrupted, while the Shi’ah group views the sanad of valid hadiths when it is connected to the Prophet or imam ma’sum without being interrupted. Sunnis also have the view that all companions are credible, while Shi’ah is not.